Midwifery tutors' capacity and willingness to teach contraception, post-abortion care, and legal pregnancy termination in Ghana - Mitchell Ellen; Mills Joseph; Yellu Nathaniel; Voetagbe Gertrude; Adu-Amankwah Amanda; Jehu-Appiah Koma; Nyante Felix (BMC, 2010)
Abstract Background Ghana has a high maternal mortality rate of 540 per 100 000. Although abortion complications usually are treatable, the risks of morbidity and death increase when treatment is delayed. Delay in care may occur when women have difficulty accessing treatment because health care providers are not trained, equipped, or willing to treat the complications of abortion. Gaps in the midwifery tutors' knowledge on comprehensive abortion care (CAC) have resulted in most midwives in Ghana not knowing the legal indications under which safe abortion care can be provided, and lacking the skills and competencies for CAC services. The aim of this study is to assess the capacity and willingness of midwifery tutors to teach contraception, post abortion care and legal termination in Ghana. Methods This study focused on all 14 midwifery schools in the country. A total of 74 midwifery tutors were interviewed for this study. Structured self-administered questionnaires were used for data collection. The data were entered and checked for consistencies using Epiinfo 6.04 and analyzed using Stata 8. Descriptive analysis was used and frequencies reported with percentages. Results In total, 74 midwifery tutors were interviewed. Of these, 66 (89.2%) were females. The tutors had mainly been trained as midwives (51.4%) and graduate nurses (33.8%). Respondents were predominantly Christians (97.3%). The study discovered that only 18.9% of the tutors knew all the legal indications under which safe abortion care could be provided. The content of pre-service training of tutors did not include uterine evacuation with manual vacuum aspirator (MVA). The study also highlighted some factors that influence midwifery tutors' willingness to teach comprehensive abortion care. It was also revealed that personal and religious beliefs greatly influence teaching of Comprehensive Abortion Care. Conclusion The findings of this survey suggest that the majority of tutors did not know the abortion law in Ghana as well as the Ghana Health Service Reproductive Health Standards and Protocol. Thus, there is a need to enhance their capacities to teach the present pre-service students the necessary skills to offer CAC after school and to understand related issues such as related legal matters.